The Gut Microbiome in Patients With Chronic Pancreatitis Is Characterized by Significant Dysbiosis and Overgrowth by Opportunistic Pathogens. Issue 9 (16th September 2020) - Frost, Fabian; Weiss, Frank U.; Sendler, Matthias; Kacprowski, Tim; Rühlemann, Malte; Bang, Corinna; Franke, Andre; Völker, Uwe; Völzke, Henry; Lamprecht, Georg; Mayerle, Julia; Aghdassi, Ali A.; et al.
Abstract : INTRODUCTION: Exocrine pancreatic function is a critical host factor in determining the intestinal microbiota composition. Diseases affecting the exocrine pancreas could therefore influence the gut microbiome. We investigated the changes in gut microbiota of patients with chronic pancreatitis (CP). METHODS: Patients with clinical and imaging evidence of CP (n = 51) were prospectively recruited and compared with twice the number of nonpancreatic disease controls matched for distribution in age, sex, body mass index, smoking, diabetes mellitus, and exocrine pancreatic function (stool elastase). From stool samples of these 153 subjects, DNA was extracted, and intestinal microbiota composition was determined by bacterial 16S ribosomal RNA gene sequencing. RESULTS: Patients with CP exhibited severely reduced microbial diversity (Shannon diversity index and Simpson diversity number, P < 0.001) with an increased abundance of facultative pathogenic organisms ( P < 0.001) such as Enterococcus ( q < 0.001), Streptococcus ( q < 0.001), and Escherichia.Shigella ( q = 0.002). The CP-associated changes were independent of exocrine pancreatic insufficiency. Short-chain fatty acid producers, considered protective for epithelia such as Faecalibacterium ( q < 0.001), showed reduced abundance in patients with CP. Of 4 additional patients with CP previously treated with antibiotics (ceftriaxone and metronidazole), 3 patients were characterized by distinct Enterococcus overgrowth. DISCUSSION: CP is associated with marked gut microbiota dysbiosis, greatly reduced diversity, and increased abundance of opportunistic pathogens, specifically those previously isolated from infected pancreatic necrosis. Taxa with a potentially beneficial role in intestinal barrier function are depleted. These changes can increase the probability of complications from pancreatitis such as infected fluid collections or small intestinal bacterial overgrowth (see Graphical Abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A383 ).